Studi Penilaian Klinis Penggunaan Antibiotik pada Pasien Penyakit Ginjal Kronis - Mita Restinia; Henny Lucida; Wasif Gillani S (Fakultas Farmasi Universitas Pancasila, 2017)
A 6-week longitudinal prospective study was conducted to assess the effectiveness and the safety antibiotic used in chronic kidney disease (CKD) patients in internal medicine ward. We compared white blood count and glomerular fi ltration rate before and after antibiotic used. The CKD patients who admitted in the internal medicine ward and age ≥18 years old were included this study. Patients with incomplete laboratory data and renal replacement therapy were excluded in this study. The 25 patients who enrolled in this study were recruited. The majority gender of CKD was male (64%), the mean of age was 61.52±14.17 years old with length of stay (LOS) was 6.92±4.05 days. The highest number of patients was in CKD stage 3 (n=10, 40%) and was followed by CKD stage 2 (n=6, 24%). Most of them were diagnosed community acquired pneumonia. Tablet azithromycin (n=16, 64%) then Cefotaxime intra venous injection (IV) (n= 6, 24%), and Ceftazidime IV (n=5, 20%), Cloxacillin IV (n=4, 16%) were the most antibiotics prescribed. Generally patients had been prescribed appropriate dose of antibiotic and 88% of them showed improved white blood count. In contrast, the glomerular fi ltration rate of 44% CKD patients was getting worse. In conclusion, this study clearly indicate the CKD patients require close monitoring to maintenance of renal function even the antibiotic had been prescribed appropriately.